DEVELOPING READING COMPREHENSION QUESTIONS OF PROCEDURE TEXT USING HIGHER ORDER THINKING SKILL IN ENGLISH TEXTBOOK OF GRADE ELEVEN AT SMA YAYASAN NURUL ISLAM INDONESIA BARU MEDAN - Afanin Nabila; Rahmad Husein (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The development of HOTS-based text questions is considered very important to be developed for high school students. based on the objectives of the 2013 Curriculum education unit which states that "The management and implementation of education aims to build a foundation for the development of the potential of students to become human ... knowledgeable, competent, critical, creative, and innovative ..." (PP No. 17 of 2010), then Therefore, it is necessary to develop HOTS-based text questions in order to achieve this goal. HOTS (Higher Order Thinking Skill) is a high-level thinking ability that must be achieved by students. This study aims to develop HOTS-based test questions proposed by Bloom's revisions C4 (analyze), C5 (evaluate), C6 (create). This study uses the type of research and development proposed by Borg and Gall (1985). The first stage in the preliminary study obtained data from interviews and documentation studies. In the second stage, the question development process is carried out together with the teacher. Phase three, revising and validating it to match the learning indicators.